2015
DOI: 10.4103/0970-2113.164155
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of prevalence, determinants, and outcomes of infections in medical ICU at a tertiary care hospital in India

Abstract: Objectives:To determine the prevalence of infections, risk factors, and outcomes in a medical intensive care unit (ICU), we performed a hospital-based study.Materials and Methods:Consecutive patients were enrolled and details of risk factors and bacteriological data were obtained. Outcomes were death/transfer to palliative care or recovery. Statistical analyses were performed.Results:Four hundred and eighty-seven patients were admitted during the study period (age 55.6 ± 19 yr, men 68%). Diseases responsible w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
20
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 34 publications
8
20
0
7
Order By: Relevance
“…It has uncanny ability to survive for prolonged periods in hospital environment [16][17][18]. The organism commonly targets the most vulnerable hospitalized patients, those who are critically ill with breaches in skin integrity and airway protection [15]. In our study, it was seen that 90% of infections occurred among the patients in ICUs, who were also on mechanical ventilation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It has uncanny ability to survive for prolonged periods in hospital environment [16][17][18]. The organism commonly targets the most vulnerable hospitalized patients, those who are critically ill with breaches in skin integrity and airway protection [15]. In our study, it was seen that 90% of infections occurred among the patients in ICUs, who were also on mechanical ventilation.…”
Section: Discussionmentioning
confidence: 65%
“…The study was focused on nosocomial lower respiratory infections due to Acinetobacter baumannii. Among the nosocomial infections, pneumonia is the most common and the organisms are most commonly are gram negative, particularly Acinetobacter baumannii in ICUs [15]. All the Acinetobacter baumannii infections were nosocomial.…”
Section: Discussionmentioning
confidence: 99%
“…Shivesh P et al, 9 reported 15% and Shashikala et al, 10 found 10.9% carbapenem resistance in their respective studies. In a study by Sachin Kumar Wankhede et al, 11 found 19.40% carbapenem resistant. Resistance to carbapenem in this study is low compared to studies from India.…”
Section: Discussionmentioning
confidence: 96%
“…Recent data from the Indian intensive care unit (ICU) setting shows that most of the pathogens are resistant to common antibiotics. [1] Empirical broad spectrum antimicrobial therapy is one of the causes responsible for this. Unusual infections are encountered more frequently now because of increased survival in acquired immunodeficiency syndrome (AIDS) patients, incidence of organ transplants, and emergence of newer viruses with atypical imaging features.…”
Section: Introductionmentioning
confidence: 99%